Serum sphingolipid profiling as a novel biomarker for metabolic syndrome characterization - Berkowitz, Loni; Salazar, Cristian; Ryff, Carol D.; Coe, Christopher L.; Rigotti, Attilio (Frontiers in Cardiovascular Medicine, 2022)
Background: Sphingolipids are components of cell membrane structure, but also circulate in serum and are essential mediators of many cellular functions. While ceramides have been proposed previously as a useful biomarker for cardiometabolic disease, the involvement of other sphingolipids is still controversial. The aim of this study was to investigate the cross-sectional association between blood sphingolipidomic profiles and metabolic syndrome (MetS) as well as other atherosclerotic risk factors in a large population-based study in the U.S. Methods: Clinical data and serum sphingolipidomic profiling from 2063 subjects who participated in the biomarker project of the Midlife in the United States (MIDUS) study were used. Results: Consistent with previous reports, we found a positive association between most ceramide levels and obesity, atherogenic dyslipidemia, impaired glucose metabolism, and MetS prevalence. In contrast, most simple β-glycosphingolipids (i.e., hexosylceramides and lactosylceramides) were inversely associated with dysmetabolic biomarkers. However, this latter sphingolipid class showed a positive link with inflammatory and vascular damage-associated biomarkers in subjects with MetS. Through metabolic network analysis, we found that the relationship between ceramides and simple β-glycosphingolipids differed significantly not only according to MetS status, but also with respect to the participants’ C-reactive protein levels. Conclusion: Our findings suggest that a comprehensive sphingolipid profile is more informative about MetS than ceramides alone, and it may reveal new insights into the pathophysiology and further diabetic versus cardiovascular risk in patients with MetS. Fundings: National Institute on Aging (P01-AG020166 and U19-AG051426) and National Fund of Scientific and Technological Development FONDECYT Chile (Postdoc 3210391).